Human Epidermal Growth Factor Receptor 2 Overexpression and Amplification in Patients With Colorectal Cancer: A Large-Scale Retrospective Study in Chinese Population - Ni, Shujuan; Wang, Xin; Chang, Jinjia; Sun, Hui; Weng, Weiwei; Wang, Xu; Tan, Cong; Zhang, Meng; Wang, Lei; Huang, Zhaohui; Huang, Dan; Xu, Midie; et al. (Frontiers in Oncology, 2022)
Background Cumulative evidence in colorectal cancer (CRC) suggests that patients with human epidermal growth factor receptor 2 (HER2) overexpression or amplification can benefit from anti-HER2 therapy. The purpose of our study was to evaluate HER2 status and its correlation with clinicopathological characteristics and survival according to currently utilized HER2 diagnostic criteria in a large cohort of Chinese CRC patients. Methods HER2 protein expression was tested by immunohistochemistry (IHC) in formalin-fixed, paraffin-embedded (FFPE) samples from 4,836 CRC patients in our institution. Breast cancer (BC) and gastroesophageal adenocarcinoma (GEA) criteria, as well as the HERACLES criteria, were used for the determination of HER2 status. Dual-color silver-enhanced in situ hybridization (DSISH) was performed in all IHC 2+ 3+ cases determined by BC/GEA criteria. Results The HER2 expression rate of IHC (1+ 3+) was 7.01% (339/4,836) and 6.02% (291/4,836) in CRCs based on the BC/GEA criteria and the HERACLES criteria, respectively, while combined DSISH results in the HER2 amplification/overexpression ratio of 3.39% (164/4,836) in our cohort. HER2 expression detected by IHC was positively correlated with the female gender, whereas the HER2 overexpression/amplification showed no correlation with any clinicopathological parameter. In addition, no significant correlation was found between HER2 statuses and either disease-free survival or overall survival regardless of the evaluation criterion used. However, patients with HER2 1+ CRC showed a tendency of having the shortest overall survival as compared with any other group of patients according to the HERACLES criteria, and this trend has always existed in the rectal location, T3 stage, and TNM stage II, medium differentiation, and perineural invasion stratified group. Furthermore, the HER2 protein expression was significantly negatively correlated with RAS/BRAF mutations according to the HERACLES criteria. Conclusion To our knowledge, this is the largest study of HER2 status in Asian patients with CRC. Our findings suggest that the current most commonly used HERACLES criteria might be too strict for patients with CRC. Future studies are needed to explore the most suitable criteria for screening CRC patients who could benefit from anti-HER2 therapy as much as possible.